Efficacy and safety of enzyme replacement therapy with alglucosidase alfa for the treatment of patients with infantile-onset Pompe disease: a systematic review and metanalysis - Dornelles, A. D.; Junges, A. P. P.; Krug, B.; Gonçalves, C.; de Oliveira Junior, H. A.; Schwartz, I. V. D. (Frontiers in Pediatrics, 2024)
Pompe disease (PD) is a glycogen storage disorder caused by the deficient activity of acid alphaglucosidase (GAA). We sought to review the latest available evidence on the safety and efficacy of recombinant human GAA enzyme replacement therapy (ERT) for infantile-onset PD (IOPD). Methods: We systematically searched the MEDLINE (via PubMed) and Embase for prospective clinical studies evaluating ERT for IOPD on pre-specified outcomes. Meta-analysis was also performed. Results: Of 1722 articles identified, 16 were included, evaluating 316 patients. Studies were heterogeneous and with very low certainty of evidence for most outcomes. Moderate/high risk of bias were present for most included articles. The following outcomes showed improvements associated with alglucosidase alfa, over natural history of PD/placebo, for a mean follow-up of 48.3 months: left ventricular (LV) mass [mean change 131.3 g/m² (95% confidence interval [CI] 81.02, 181.59)], time to start ventilation (TSV) [HR 0.21 (95% CI 0.12, 0.36)] and survival [HR 0.10 (95% CI 0.05, 0.19)]. There were no differences between the pre-and post-ERT period for myocardial function and psychomotor development. Adverse events (AEs) after ERT were mild in most cases. Conclusion: Our data suggest that alglucosidase alfa potentially improves LV mass, TSV, and survival in IOPD patients, with no important safety issues. PROSPERO register: 42019123700.